Influence of Organizational Culture and Transformational Leadership on Employee Performance through Job Satisfaction as an Intervening - Pratama, R. Dandy Jurindra; Tridayanti, Hermien; Suyono, Joko; Sumarno, Sumarno; Salamin, Akhmad Lutfis (INNOVATION RESEARCH JOURNAL, 2025)
his study examines the influence of organizational culture and transformational leadership on employee performance, with job satisfaction as an intervening variable, at Dinas Sumber Daya Air dan Bina Marga Surabaya. The research focuses on 176 permanent employees using saturated sampling, where the entire population is included. Data were collected through direct questionnaires, allowing respondents to provide feedback, and were analyzed using path analysis with multiple linear regression in SPSS version 17.0. The results indicate that both organizational culture and transformational leadership positively impact job satisfaction and employee performance. However, job satisfaction mediates the effect of transformational leadership on performance but not the effect of organizational culture. The study highlights the importance of fostering a dynamic learning culture to improve job satisfaction and performance. It suggests the Surabaya City Government continue focusing on these factors to enhance overall organizational outcomes.